Integrated risk management in the digital era: leveraging on business model canvas for a property developing company - Mahmood Dean, Muhammmad Khair; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2020)
The risk of unexpected and harmful events haunted every business that will cost the company money or ultimately brings it to permanently close. Risk management allows organizations to get ready for the unforeseen events by minimizing and avoiding the risks before they happen. The implementation of a successful risk management plan will ensure an organization is saved from catastrophic consequences, thus protecting the company’s future. The aim of this paper is to review the risk management in a particular property developing company in Malaysia and subsequently making this type of company relevance in the digital era. Disruptive forces such as IR4.0 and new business models can pave the way for explosive growth or take down reputable giants. Having a strategy in place to identify, address and harnessing on these emerging and disruptive forces, analyze and prioritize their importance, understand their long-term implications, highlight and plan for action with enterprise risks management is imperative for thriving in the digital era. For the purpose of this paper, the name of the company will not be disclosed. This paper will discuss on the business model options of the Property Development-of-the-Future (PDotF) by using the business model canvas (BMC) framework, together with its new risks and challenges. This business model may facilitate and help PDotF in identifying the key assets, thus as an enabler the formulation of an effective enterprise risk management system.